Design and Analysis of a Database to Evaluate Children's Reading Aloud Performance - Proença, Jorge; Celorico, Dirce; Lopes, Carla; Dias, Miguel Sales; Tjalve, Michael; Stolcke, Andreas; Candeias, Sara; Perdigão, Fernando (Proc. PROPOR'2016 - 12th International Conference on the Computational Processing of Portuguese, 2016)
To evaluate the reading performance of children, human assessment is usually involved, where a teacher or tutor has to take time to individually estimate the performance in terms of fluency (speed, accuracy and expression). Automatic estimation of reading ability can be an important alternative or complement to the usual methods, and can improve other applications such as elearning. Techniques must be developed to analyse audio recordings of read utterances by children and detect the deviations from the intended correct reading i.e. disfluencies. For that goal, a database of 284 European Portuguese children from 6 to 10 years old (1st-4th grades) reading aloud amounting to 20 hours was collected in private and public Portuguese schools. This paper describes the design of the reading tasks as well as the data collection procedure. The presence of different types of disfluencies is analysed as well as reading performance compared to known curricular goals.